Absolute values of economy indices in rowing - Bingelis, A.; Danisevicius, J. (Education. Physical training. Sport, 1999)
An improved methematical model of the heaving during the process of rowing is analysed in the paper. The influence of the stroke rate, the vertical force on the seat and the mass of the crew on the absolute values of the economy in rowing has been calculated. The economy in rowing different classes of boats has been compared. Without repeating the conclusions and recomendations presented in the previous publications the results of this study allow us to make the following conclusions: having assumed the coefficient of efficiency in deal rowing conditions as being equal to 1, the dispersed values of this coefficient amouting to less than 1 could be used for estimating the real conditions of rowing. The dependence and range of variation of these values have been indicated in the discusion of the results gained by this study. The absolute values of the coefficients of efficiency of rowing point to a different economy in rowing boats belonging to various classes fot the real values of the boat complex mass, stroke rate and the vertical force on the seat. Having subdivided all rowboats into big and small ones on the basis of the character of the effect of heaving it can be asserted that this effect is more variable and exerts a greater influence on small boats then on big ones. Address correspondence to: Algirdas Bingelis, Sporto 6, LT-3000 Kaunas, Lithuania Fax: (370-7) 204515, E-mail: bingelis@lkki.lt (from: Education. Physical Training. Sport, 1999, 1(30), 5-11)